Crystallographic and spectroscopic characterization of a molecular hinge: Conformational changes in Bothropstoxin I, a dimeric Lys49- phospholipase A2 homologue - Da Silva Giotto, M. T.; Garratt, R. C.; Oliva, G.; Mascarenhas, Y. P.; Giglio, J. R.; Cintra, A. C.O.; De Azevedo, W. F. [UNESP]; Arni, R. K. [UNESP]; Ward, R. J. [UNESP] (My University, 1998)
Bothropstoxin I (BthTX-I) from the venom of Bothrops jararacussu is a myotoxic phospholipase A2 (PLA2) homologue which, although catalytically inactive due to an Asp49→Lys substitution, disrupts the integrity of lipid membranes by a Ca2+-independent mechanism. The crystal structures of two dimeric forms of BthTX-I which diffract X-rays to resolutions of 3.1 and 2.1 Å have been determined. The monomers in both structures are related by an almost perfect twofold axis of rotation and the dimer interfaces are defined by contacts between the N-terminal α-helical regions and the tips of the β- wings of partner monomers. Significant differences in the relative orientation of the monomers in the two crystal forms results in 'open'and 'closed' dimer conformations. Spectroscopic investigations of BthTX-I in solution have correlated these conformational differences with changes in the intrinsic fluorescence emission of the single tryptophan residues located at the dimer interface. The possible relevance of this structural transition in the Ca2+-independent membrane damaging activity is discussed.
Keywords: Protein-membrane interaction; Quaternary structural change; Spectroscopy; Venom toxin; X-ray diffraction